2018
DOI: 10.4034/pboci.2018.181.46
|View full text |Cite
|
Sign up to set email alerts
|

Mouth Breathing and Prevalence of Sleep Bruxism among Preschoolers aged 2 to 5 years

Abstract: Objective: To determine the prevalence of bruxism, associating it with mouth breathing in preschool children in Florianopolis, Brazil. Material and Methods: Clinical examination and questions to parents/guardians of 429 children aged 2-5 were conducted. The clinical examination was performed by three calibrated examiners to register the presence of tooth wear on incisors and molars. The questions were related to sleep bruxism (teeth grinding) and mouth breathing. For determinate diagnosis, were "possible" brux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This result is in agreement with results of the previous studies Seraj et al, (2010), Vieira-Andrade et al, (2014), and Miamoto et al, (2011) which showed that no significant association between age and bruxism in a pediatric population (19)(20)(21). In contrast, this result disagreed with Soare et al, (2018) (22) who found a significant relationship between age and bruxism.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result is in agreement with results of the previous studies Seraj et al, (2010), Vieira-Andrade et al, (2014), and Miamoto et al, (2011) which showed that no significant association between age and bruxism in a pediatric population (19)(20)(21). In contrast, this result disagreed with Soare et al, (2018) (22) who found a significant relationship between age and bruxism.…”
Section: Discussionsupporting
confidence: 89%
“…This result agreed with the previous studies by Fonseca et al, (2011), Seraj et al, (2010) and Demirbag et al, (2014) which showed that no significant association between gender and bruxism (16,19,23). On the contrary to some researchers Cheifetz et al, (2005) (24) and Soares et al, (2018) (22) who reported bruxism is more prevalent in boys. This may be due to different sample sizes, and conduction of the study in the pediatric dental offices.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation